Study on Growth of Large-Leaved Mangrove (Rhizophora mucronata) from Granular Chicken Manure and Phosphate Fertilizer - นิ่มรัตน์, สุบัณฑิต; กิติสาร, ชุติมา; วุฒิพันธุ์ชัย, วีรพงศ์ (KKU Science Journal, 2015)
In this study, the effect of granular chicken manure and super phosphate fertilizer (P2O5) on the growth of Rhizophora mucronata was assayed. The experimental design was assigned as completely randomized design (CRD) with four treatments including C (control), T1 (using 250 kg/Sq Mts of granular chicken manure), T2 (using 50 kg/Sq Mts of super phosphate fertilizer) and T3 (using 250 kg/Sq Mts of granular chicken manure and 50 kg/Sq Mts of super phosphate fertilizer) for 90 days. The results of growth parameters revealed that T2 had the most fresh weight of pods (39.77±4.77 g) and dry weight of stem and roots (84.73±7.76 g). T3 had the highest plant height with 26.30±0.20 cm and T1 had the highest leaf area with 42.20±2.15 cm2. In addition, the study of soil properties after planting R. mucronata on Day 70 showed that T1 had the highest value of ammonium, while T3 demonstrated the highest value of phosphorus. Soil texture was determined as sandy soil over a period of 90 days. Total heterotrophic bacteria of T3 had the highest level with (234.00±1.00)×103 CFU/g on Day 4. Therefore, the results of this study shown that granular chicken manure and super phosphate fertilizer are capable of enhancing the growth of Rhizophora mucronata, which can used further as a guideline for leading to the development and conservation of important mangrove plants in Thailand.